MODERATING EFFECTS OF JOB GRADES ON THE RELATIONSHIP BETWEEN DARK TRIAD, ANOMIA, NEGATIVE AFFECTIVITY ON TYPE S COUNTERPRODUCTIVE WORK BEHAVIOUR (CWB-S) - Narehan Hassan,; Azwan Shah Aminuddin,; Abdul Kadir Othman, (Journal of Islamic, Social, Economics and Development, 2024)
Despite the fact that some researchers have gained notoriety by employing certain approaches and focusing on particular Counterproductive Work Behaviours (CWBs), the study focused on the differences discovered in individual personalities that motivate people to engage in CWB-S. Job grades were also investigated to determine their impacts on the existing link between individual differences and work-related behaviours in order to have a better understanding of how CWB-S and individual differences are connected to one another. The Dark Triad, which consists of Machiavellianism, Narcissism, and Psychopathy, together with Anomia and Negative Affectivity were the independent variables in this study. Meanwhile, job grades (Grades 1, 2, and 3) were employed as the moderating variables. The stratified quota sampling technique was used to select 588 respondents and their responses were collected via online questionnaire survey. The findings of this study should help other scholars to conduct research in this field using other factors and comprehend the topic of Type S Counterproductive Work Behaviours (CWB-S) more thoroughly. It is recommended that further investigation needs to explore the influence of other job factors such as reward programmes or job characteristics, also expanding the samples to other categories with larger samples pertaining to higher-ranking employees.